RENTAL INFORMATION SYSTEM TOOLS PARTY ON CV. ANDAYA PURI - Hari Kapriyadi; Susi P. Wagiyati, SKom, MMSi (Jurnal Sistem Informasi, 2002)
CV. Andaya Puri is an enterprise that is engaged in equipment leasing party. Butthere are still deficiencies in the management of the provision of information on thenumber and types of equipment.The purpose of writing this research is to present the numbers and types of equipmentwill be rented to customers and the relevant sections.Based on the constraints faced by authors propose a change from the old system wasin process list of party rental equipment, checking and producing computerizedreports using Access Micrososft applications.Hopefully, with computer tools can help to work in accordance with companyexpectations.